Coherent spin-exchange via a quantum mediator - Baart, Timothy Alexander; Fujita, Takafumi; Reichl, Christian; Wegscheider, Werner; Vandersypen, Lieven Mark Koenraad (Nature nanotechnology, 2017)
Two electron spins occupying the outer dots in a linear array of three quantum dots experience a coherent superexchange interaction through the empty middle dot that acts as a quantum mediator. Coherent interactions at a distance provide a powerful tool for quantum simulation and computation. The most common approach to realize an effective long-distance coupling ‘on-chip’ is to use a quantum mediator, as has been demonstrated for superconducting qubits 1 , 2 and trapped ions 3 . For quantum dot arrays, which combine a high degree of tunability 4 with extremely long coherence times 5 , the experimental demonstration of the time evolution of coherent spin–spin coupling via an intermediary system remains an important outstanding goal 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 . Here, we use a linear triple-quantum-dot array to demonstrate a coherent time evolution of two interacting distant spins via a quantum mediator. The two outer dots are occupied with a single electron spin each, and the spins experience a superexchange interaction through the empty middle dot, which acts as mediator. Using single-shot spin readout 26 , we measure the coherent time evolution of the spin states on the outer dots and observe a characteristic dependence of the exchange frequency as a function of the detuning between the middle and outer dots. This approach may provide a new route for scaling up spin qubit circuits using quantum dots, and aid in the simulation of materials and molecules with non-nearest-neighbour couplings such as MnO (ref. 27 ), high-temperature superconductors 28 and DNA 29 . The same superexchange concept can also be applied in cold atom experiments 30 .